Soil Mineral Microbe-Organic Interactions - Huang, Qiaoyun (Springer, 2017)
The book presents the latest research findings and prospects on soil mineral-organic matter-microorganism interactions. It includes topics covering mechanisms of transformations, dynamics and bioavailability of heavy metals, radionuclides, biomolecules and nutrients immobilized on soil minerals, humic substances, mineral-humic complexes and microorganisms and their impact on plant, animal and human health. The book contains six parts: 1) Transformation and dynamics of pollutants in soil environments, 2) Chemical, biological and biochemical processes in the rhizosphere, 3) Bioavailability of metals and xenobiotics immobilized on soil components, 4) Distribution and activity of biomolecules in terrestrial systems, 5) Interactions between soil microbial biomass and organic matter/nutrient transformations, and 6) Impact of interactions among soil mineral colloids, organic matter and biota on risk assessment and restoration of terrestrial ecosystems.